Association of oxidative status and insulin sensitivity in periparturient dairy cattle: an observational study. Issue 2 (14th July 2015) - Abuelo, A.; Hernández, J.; Benedito, J. L.; Castillo, C.
Summary: Post‐parturient insulin resistance (IR) is a common feature in all mammalian animals. However, in dairy cows, it can be exacerbated because of high milk yield, leading to excessive negative energy balance, which is related with increased disease incidence, reduced milk production and worsened reproductive performance. IR has been extensively investigated in humans suffering from diabetes mellitus. In these subjects, it is known that oxidative stress (OS) plays a causative role in the onset of IR. Although OS occurs in transitional dairy cattle, there are yet no studies that investigated the association between IR and OS in dairy cattle. Therefore, the aim of this study was to investigate whether there is a relationship between OS and IR in dairy cattle. Serum samples were taken repeatedly from 22 dairy cows from 2 months prior to the expected calving date to 2 months after calving and were analysed for markers of metabolic and redox balance. Surrogate indices of insulin sensitivity were also calculated. Generalised linear mixed models revealed an effect of the oxidative status on peripheral insulin concentration and on indices of insulin sensitivity. Hence, field trials should investigate the effectiveness of antioxidant therapy on insulin sensitivity in peripheral tissues during the transition period of dairy cattle.